Effect of Using Personal Protective Equipment during the COVID-19 Pandemic on the Quality Indicators of Screening Colonoscopies - Subin Chirayath; Janak Bahirwani; Parampreet Kaur; Noel Martins; Ronak Modi (Gastroenterology Research and Practice)
Background. Coronavirus Disease 2019 (COVID-19) has affected many facets of the practice of medicine including screening colonoscopies. Aims. Our study looks to observe if there has been an effect on the quality of colonoscopies, as indicated by quality measures such as the cecal intubation rate (CIR), cecal intubation time (CIT), scope withdrawal time (SWT), and adenoma detection rate (ADR) with the adoption of standard COVID-19 precautions. Methods. We conducted a retrospective chart review to analyze the effects of the COVID-19 pandemic on screening colonoscopies. The study utilized data on CIR, CIT, SWT, and ADR from outpatient, nonemergent procedures conducted at 3 endoscopy suites of St. Luke’s University Health Network. All inpatient and emergent procedures were excluded. Results. Our study demonstrated that the total number of screening colonoscopies was decreased between 2019 and 2020 (318 in 2019 vs. 157 in 2020, p=0.005). CIT (320±105 seconds in 2019 vs. 392±107 seconds in 2020, p=0.001) and SWT (706±232 seconds in 2019 vs. 830±241 seconds in 2020, p=0.001) were increased while CIR (98.2% in 2019 vs. 96.6% in 2020, p=0.04) was decreased between 2019 and 2020 likely due to PPE introduction. ADR was similar between the two groups (38.23 (12.50-66.66) in 2019 vs. 38.18 (16.66-66.00) in 2020, p=0.8). Conclusion. Our study showed that quality indices for screening colonoscopies like CIR, CIT, and SWT were negatively impacted during the COVID-19 time period. ADR, however, was similar. Thus, the efficiency of the procedures was affected by the use of PPE but it did not affect the colonoscopy’s clinical benefit.